Emerging equity markets : growth, benefits, and policy concerns. - FELDMAN, Robert A. (1995)
Examines the main characteristics of emerging stock markets and illustrates the evolution of equity prices in these markets during the last decade. Discusses reasons for the markets' growth, and assesses the extent to which they have been affected by domestic policies and external factors. Identifies likely benefits of these markets, the effects any abrupt correction in stock prices could have for the economy, and the ways in which these markets can be made more efficient.